Bound biblio parent record 9401BEEB - Aho, Jouko; Katermaa, Aino; Laisi, Helena; Endén, Rauno; Suomen historiallinen seura (Historiallinen arkisto, ISSN 0073-2540, 1989)
Summaries in English.
Keywords: Bolin, Wilhelm; Soldan, August Fredrik; Hällstén, Konrad Gabriel; Rein, Thiodolf; Tigerstedt, Robert; Neiglick, Hjalmar; Nordman, Gustaf; Selander, Edvard; Grotenfelt, Arvi; 1700-luku; psykologia; tiedemiehet; paikallishistoriat (historiikit); kaavoitus; työväenyhdistykset; oppihistoria; historia; varallisuus; Hämeenlinna